Virtual English as a Lingua Franca: Investigating the Discourse of Digital Exchanges and Understanding Technology- Enhanced Learning. - Pineda-Hernández, Inmaculada Concepción; Rino, Bosso (Routledge, 2023)
How do people make pragmatic meaning in an interconnected, English-speaking, and technology-enhanced globalized world? How do they manage to achieve their communicative goals when engaging in exchanges with Internet users of different linguacultural backgrounds? And what learning can be derived from observing their naturally occurring interactions? This introductory chapter discusses the different theoretical frameworks that inform the research presented in the current volume, it provides definitions of terms and processes that will be later addressed in the chapters. It is particularly original as it develops the concept of Virtual English as a lingua franca (VELF) and it describes the trans- practices that have been identified in the research presented below. This introduction also anticipates the central issues around which the book is structured. Transmodal, translingual and transcultural discourse practices in online settings are described with the intention of prompting readers to reflect on these and relate them with their own experience with VELF exchanges. It is a section that introduces researchers and postgraduate students to the strategies of online intercultural communication in the 21st century, pragmatic processes and practices that they will likely experience and engage in both in their private and professional lives.
Keywords: Medios de comunicación social y lenguaje; English as a lingua franca; Communication strategies on Social Media; Translingual practice; Transmodal practice